The leading edge of early childhood education : linking science to policy for a new generation - Lesaux, Nonie K.; Jones, Stephanie M. (Harvard Education Press, 2016)
The Leading Edge of Early Childhood Education aims to support the effort to simultaneously scale up and improve the quality of early childhood education by bringing together relevant insights from emerging research to provide guidance for this critical, fledgling field. Reflecting the growing recognition that early child- hood experiences have a powerful affect on children's later academic achievement and long-term life outcomes, this book promises to be a valuable resource for those charged with enacting the next level of work in this critical area.